2023
DOI: 10.3389/fpsyt.2023.1071181
|View full text |Cite
|
Sign up to set email alerts
|

The global prevalence of autism spectrum disorder: A three-level meta-analysis

Abstract: Autism spectrum disorder (ASD) is one the most disabling developmental disorders, imposing an extremely high economic burden. Obtaining as accurate prevalence estimates as possible is crucial to guide governments in planning policies for identification and intervention for individuals with ASD and their relatives. The precision of prevalence estimates can be heightened by summative analyses of the data collected around the world. To that end, we conducted a three-level mixed-effects meta-analysis. A systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 108 publications
0
22
0
Order By: Relevance
“…4 Over the past ten years, there has been a steady increase in the prevalence of ASD, which has led to serious financial strain on families and society. 5 To date, the pathophysiology of ASDs has not been fully resolved; however, an expanding corpus of data indicates that numerous events early in life may be connected to the beginning and advancement of ASD. Epidemiologic investigations have shown that preterm birth and older maternal age are risk factors for ASD, 6,7 and prenatal exposure to air pollution and short gestational intervals are also potential risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…4 Over the past ten years, there has been a steady increase in the prevalence of ASD, which has led to serious financial strain on families and society. 5 To date, the pathophysiology of ASDs has not been fully resolved; however, an expanding corpus of data indicates that numerous events early in life may be connected to the beginning and advancement of ASD. Epidemiologic investigations have shown that preterm birth and older maternal age are risk factors for ASD, 6,7 and prenatal exposure to air pollution and short gestational intervals are also potential risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, while the WHO (2023) estimates that 1 in 100 children has ASD, the Centers for Disease Control and Prevention (CDC, 2021) estimates that 1 in 44 children is diagnosed with some form of ASD. Many factors are thought to account for these differences in prevalence, such as the population sampled, the study design, and the diagnostic criteria used (Elsabbagh et al, 2012;Talantseva et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies suggest that the prevalence of autism is increasing (CDC, 2021;Elsabbagh et al, 2012;Fajardo et al, 2021;Talantseva et al, 2023). The explanations for this phenomenon are diverse, ranging from expansions in diagnostic criteria (such as increased diagnoses of ASD and decreased diagnoses of Intellectual disability), environmental factors (such as increased survival rates of premature babies, who have a higher incidence of ASD, as found byWang et al, 2017), advanced parental age (as reported byKim et al, 2019), and increased awareness of the disorder and access to healthcare services F84.5), other PDD (F84.8), and PDD not otherwise speci ed (PDD-NOS, F84.9).…”
mentioning
confidence: 99%
“…Autism spectrum disorder (ASD) is characterized by 2 core areas of symptoms: social communication impairment and restricted and repetitive behaviors or interests . In 2020, the US Centers for Disease Control and Prevention estimated that the prevalence of ASD was 1 in 36; this number continues to grow, possibly due to increased awareness among the public, medical, and research communities . The 2019 Global Burden of Disease study reported an age-standardized global ASD prevalence of 369.39 per 100 000 .…”
Section: Introductionmentioning
confidence: 99%